GPS Imaging of Vertical Bedrock Displacements: Quantification of Two‐Dimensional Vertical Crustal Deformation in China. Issue 4 (26th April 2021) - Pan, Yuanjin; Hammond, William C.; Ding, Hao; Mallick, Rishav; Jiang, Weiping; Xu, Xinyu; Shum, C. K.; Shen, Wenbin
Abstract: The Global Positioning System (GPS) derived bedrock displacements respond to multiple geophysical effects, ranging from surface elastic loads to tectonic sources or viscoelastic uplifts stemming from Earth's viscous mantle. In this study, the GPS‐inferred vertical crustal velocities are rigorously estimated in mainland China. We integrate the GPS vertical velocity field with Gravity Recovery and Climate Experiment (GRACE) and GRACE Follow‐On (GFO) data, adopting an empirical Spatial Structure Function (SSF), to image tectonic deformation in mainland China with respect to the International Terrestrial Reference Frame (ITRF) 2014. We present four profiles across China, which indicate that our new robust results are superior to kriging. Furthermore, we use the GRACE/GFO products to account for elastic deformation due to surface mass changes to isolate tectonic deformation signals at GPS sites within mainland China from 2002 to 2019. By integrating GPS and GRACE/GFO measurements, our results reveal the long‐term spatial patterns of vertical tectonic motion in different blocks in mainland China. We conclude that significant steep velocity gradients occur at tectonic block boundaries that are attributable to locking and elastic strain accumulation on active block boundary faults. Key Points: Individual GPS vertical crustal velocities are rigorously estimated in China Spatial Structure Function enabled GPS imaging provides improved estimates of the crustal deformation in China Combining GPS‐derived velocity with GRACE‐inferred deformation allows quantification of spatial patterns of tectonic block motions in China